MANAJEMEN KUALITAS MEDIA AIR BUDIDAYA IKAN LELE DENGAN METODE BIOFLOK PADA KOLAM TERPAL - Vera Viena; Tengku Mia Rahmiati; saisa saisa; Mujiburrahman Mujiburrahman (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2021)
Intensive catfish farming can cause a decrease in the water quality of the culture media, including decreasing dissolved oxygen content and increasing waste content, especially organic nitrogen. The application of Biofloc technology was carried out by the Young Independent Fish Cultivator Group (Pokdakan) with the aim of managing catfish farming activities in Lam Ara Village, Banda Raya District, Banda Aceh City using Biofloc on cultivation media. The purpose of this study was to compare the growth of catfish reared using Biofloc and non-Biofloc culture media. The test animals used in this study were catfish with Sangkuriang variety (Clarias gariepinus) measuring 7-8 cm as many as 2,000 fish in 8 different containers. Observations were made on the day of stocking until harvesting. The growth parameters observed were the length and weight of the fish. The environmental parameters observed were water temperature, dissolved oxygen, and pH. The results showed that there were differences in the increase in length and body weight of catfish in the cultivation media of Biofloc and non-Biofloc applications. The results of this study indicate that the application of the biofloc method can increase the productivity of tarpaulin ponds. The rearing media that applied the Biofloc technique showed better and relatively ideal conditions for catfish cultivation.